2022
DOI: 10.1177/22779752211073643
|View full text |Cite
|
Sign up to set email alerts
|

Do Female Board Members Influence Corporate Social Responsibility Performance?

Abstract: Caring for the environment has become everyone’s responsibility because of our significant negative impact. Considering this, companies are spending a substantial amount on corporate social responsibility (CSR) activities not only as part of corporate citizenship but also to enhance corporate image. Using a fixed-effect model on 2,260 companies’ annual data from 2012 to 2017, we analyze whether female board members influence CSR performance. The results indicate that the proportion of female board directors (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Kedua, Oino dan Liu (2022) berpendapat bahwa anggota dewan wanita mempromosikan pengambilan keputusan partisipatif dan diskusi terbuka untuk mengatasi tantangan CSR dan memberikan fasilitas pengawasan serta pengungkapan atas segala kegiatan CSR. Ketiga, perusahaan yang memiliki keragaman gender dalam dewannya akan memiliki kecenderungan untuk mempromosikan inovasi dalam strategi sosial dengan berfokus pada pandangan jangka panjang serta dampaknya terhadap kinerja lingkungan (Oino & Liu, 2022). Selain itu, keragaman gender dalam dewan juga akan mendorong peluang finansial dan sosial serta meningkatkan legitimasi dan kesuksesan perusahaan (Siboni dkk., 2016).…”
Section: Keragaman Gender Dewan (Board Gender Diversity) Dan Sustaina...unclassified
“…Kedua, Oino dan Liu (2022) berpendapat bahwa anggota dewan wanita mempromosikan pengambilan keputusan partisipatif dan diskusi terbuka untuk mengatasi tantangan CSR dan memberikan fasilitas pengawasan serta pengungkapan atas segala kegiatan CSR. Ketiga, perusahaan yang memiliki keragaman gender dalam dewannya akan memiliki kecenderungan untuk mempromosikan inovasi dalam strategi sosial dengan berfokus pada pandangan jangka panjang serta dampaknya terhadap kinerja lingkungan (Oino & Liu, 2022). Selain itu, keragaman gender dalam dewan juga akan mendorong peluang finansial dan sosial serta meningkatkan legitimasi dan kesuksesan perusahaan (Siboni dkk., 2016).…”
Section: Keragaman Gender Dewan (Board Gender Diversity) Dan Sustaina...unclassified
“…Drawing upon agency theory, BGD is a vital dimension of CG that augments board independence and monitoring by raising critical questions and opposing firms' immoral and unethical policies, positively influencing QCSD (Freeman, 1984; Issa et al, 2022; Jensen & Meckling, 1976; Nguyen et al, 2020). Many empirical studies also concluded that female directors have a significant positive effect on firms' QCSD (Issa et al, 2022; Katmon et al, 2019; Oino & Liu, 2022; Shaheen et al, 2021; Zahid, Rehman, Ali, et al, 2020), especially in countries with a weak CG structure, inferior institutional quality, and gender inequalities (Low et al, 2015; Rahman et al, 2022; Zahid, Rahman, Ali, et al, 2020). However, conversely, some researchers also documented that female directors have a negative or no relationship with QCSD due to their less aggressive and overcautious approach, which wastes the time, energy, and resources of the firms (Adams & Ferreira, 2009; Handajani et al, 2014; Khan, 2010; Yang et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirically, many studies found that highly educated female directors have a positive relationship with firms' CSR disclosure, which may be due to the good quality of their education or its better utilization in terms of decision‐making (Terjesen et al, 2009; Zhai & Gao, 2015; Zhu & Zhang, 2022). Compared to their less or low educated female colleagues, women directors with higher educational levels develop better strategies, especially in following market trends (Issa et al, 2022; Oino & Liu, 2022; Zhu & Zhang, 2022). Molinero‐Díez et al (2022) found that female directors who hold bachelor's or master's degrees improve firms' social and economic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation